2020
DOI: 10.1017/s1466252319000069
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome of the digestive system of ruminants – a review

Abstract: This review aims to explain the influence and characterization of the microbiome in the ruminant digestive system by presenting the knowledge collected so far. The knowledge presented in this work is focused on the main factors affecting the microbiome and the main dependencies that have been found in it so far. The microbiome in the rumen is the first to come into contact with the biomass of the forage and its main purpose is to decompose into smaller particles or compounds. With the gradual increase in knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 67 publications
0
60
0
Order By: Relevance
“…Microorganisms act as a specific ecosystem, which is adapted to the habitat and physiological status of the host. Populations of microorganisms include saprophytic microorganisms, commensals and incidentally pathogenic microorganisms [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms act as a specific ecosystem, which is adapted to the habitat and physiological status of the host. Populations of microorganisms include saprophytic microorganisms, commensals and incidentally pathogenic microorganisms [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results may suggest that although the Romanov sheep as a breed was in the past formed and selected for desirable traits in Russia and was then subject to conditions prevailing in this country, this could have affected the composition of its current microbiome. Despite being maintained in Poland, this could still contain the features of the microbiome from the time of breed formation in Russia [ 6 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies conducted so far have shown a significant impact of the microbiological composition of the digestive system on the health status of the animals and the quality of the products obtained from them, i.e., milk and meat, as well as the amount of methane produced [ 3 , 4 , 5 ]. Anaerobic and relatively aerobic bacteria (mainly Firmicutes and Bacteroidetes) are the most abundant, along with much smaller quantities of Proteobacteria, Fibrobacteres, Tenericutes, and Actinobacteria, followed by archeons (mainly Methanobacterium , Methanosarcina , and Methanobrevibacter species), protozoa (i.e., genus Isotrichia , Dasytrichia , Entodidium , Diplodinium , Endidiplodinium ) and fungi (e.g., Anaeromyces , Caecomyces , and Cyllamyces [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations